2021
DOI: 10.3389/fpubh.2021.667364
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Armed Conflict on the Epidemiological Situation of COVID-19 in Libya, Syria and Yemen

Abstract: Background: Since the Arab uprising in 2011, Libya, Syria and Yemen have gone through major internal armed conflicts. This resulted in large numbers of deaths, injuries, and population displacements, with collapse of the healthcare systems. Furthermore, the situation was complicated by the emergence of COVID-19 as a global pandemic, which made the populations of these countries struggle under unusual conditions to deal with both the pandemic and the ongoing wars. This study aimed to determine the impact of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 26 publications
3
35
0
Order By: Relevance
“…These results suggest that the mortality risk of COVID-19 will increase because of the escalation in conflicts. Our findings are consistent with the recent study by Daw ( 7 ) that links higher armed conflict levels to the greater spread of the COVID-19 pandemic in Libya, Syria, and Yemen. Future articles can use different indicators and econometric techniques using survey data to predict the drivers of the spread of the COVID-19 pandemic and the CFR in different countries.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results suggest that the mortality risk of COVID-19 will increase because of the escalation in conflicts. Our findings are consistent with the recent study by Daw ( 7 ) that links higher armed conflict levels to the greater spread of the COVID-19 pandemic in Libya, Syria, and Yemen. Future articles can use different indicators and econometric techniques using survey data to predict the drivers of the spread of the COVID-19 pandemic and the CFR in different countries.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Moosa and Khatatbeh ( 6 ) found that age structure and population density are the main determinants of the CFR. Daw ( 7 ) showed that armed conflict is the main determinant of the spread of COVID-19 in Libya, Syria, and Yemen. Elgar et al ( 8 ) indicated that social capital and income inequality are the main drivers of COVID-19 deaths in 84 countries.…”
Section: Introductionmentioning
confidence: 99%
“…Note that when we focus on the first difference of the series, all CFR values become stationary. The results from Malaysia, which show the predictability of the CFR values, are in line with the findings of Diaz et al ( 7 ), Sorci et al ( 9 ), Daw ( 10 ), Zhai et al ( 11 ), Khan et al ( 12 ), and Hradsky and Komarek ( 13 ). However, the findings from Indonesia and the Philippines, which provide the unpredictability of the CFR values, are in line with the previous evidence in Ioannidis et al ( 5 ).…”
Section: Empirical Findingssupporting
confidence: 90%
“…Moreover, Daw ( 10 ) shows that the conflicts raise the CFR values in Libya, Syria, and Yemen. Zhai et al ( 11 ) further develop this evidence by using the cross-section data from 120 countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation